PENERAPAN UJI KORELASI RANK SPEARMAN UNTUK MENGETAHUI HUBUNGAN PENGELUARAN RUMAH TANGGA UNTUK MAKANAN DAN TINGKAT KEMISKINAN DI NUSA TENGGARA TIMUR SELAMA PANDEMI COVID-19 - Putri Pamungkasih (Badan Pusat Statistik Provinsi NTT, 2023)
Since December 2019, a series of cases of pneumonia have emerged in China, which have been identified as the new coronavirus and are better known as Covid19 disease. This virus then spread throughout the world. On March 2 2020, Indonesia first confirmed the Covid19 case in Indonesia. Based on research and indicators produced by BPS, it can be seen that the pandemic has had an impact throughout the world, including East Nusa Tenggara. In the fourth quarter of 2020, the household consumption component experienced a contraction of 3.88 percent and in the fourth quarter of 2021 it began to improve with growth of 4.88 percent. This research is to determine household expenditure patterns in East Nusa Tenggara during the 2020-2021 Covid19 pandemic and examine whether there is a relationship with poverty levels. From the research results, it can be concluded that the average expenditure of residents in urban areas is higher than residents in rural areas. In addition, the percentage of urban residents' consumption expenditure on food is lower than expenditure on non-food. In 2020, monthly per capita expenditure on food has no correlation with the percentage level of poverty, while in 2021 monthly per capita expenditure on food has a correlation with the percentage level of the poverty. This research can still be developed by adding several other socio-economic variables to see the relationship or estimate how much influence the Covid19 pandemic has had on population consumption patterns in East Nusa Tenggara using more complex analytical tools.